The multi-faceted dimensions for the disclosure quality of non-financial information in revising directive 2014/95/EU. Issue 1 (22nd July 2021) - Fiandrino, Simona; Gromis di Trana, Melchior; Tonelli, Alberto; Lucchese, Antonella
Abstract : Purpose: The aim of this paper is to provide the state of the art in the academic and professional debate on the disclosure quality of NFI. This analysis is driven by the need to feature the dimensions of NFI quality that should be considered to improve the current regulatory framework towards a more transparent disclosure. Design/methodology/approach: The research is an integrative literature review that assesses and synthesizes the scientific knowledge and the annexed documents collected during the public consultation for the Review of Non-financial Reporting Directive (NFRD) on the disclosure quality of non-financial information (NFI). Findings: Findings show that there is a common consensus between scientific literature and the annexed documents of the consultation process on the Review of the NFRD on the need to enhance a double-materiality perspective, to provide specific contents on sustainability issues, to clarify the relevance of NFI, and to embed NFI into the management report in an integrated manner. Furthermore, there is an alignment related to timeliness in favour of a risk management procedure and a forward-looking approach. Research limitations/implications: The research engages the debate on the NFI disclosure quality, in light of the recent Review of NRFD and the new Proposal of Corporate Sustainability Reporting Directive that extends and enhances the non-binding reporting guidelines of NFI. Practical implications: The research provides a dashboard of the dimensions of NFI disclosure quality that aggregates the academics' and practitioners' knowledge systematically. It shows the interplay between the scholarly developments and the recent measures arisen in the consultation process to undertake NFI disclosure quality. Originality/value: The research provides a lens to analyse, classify and interpret the insights emerged during the consultation process of the NFRD.